1997
DOI: 10.1677/joe.0.1540415
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of natriuretic peptide receptors in eel gill

Abstract: A radioligand-binding assay was established for eel atrial natriuretic peptide (eANP), and ANP receptors were characterised in the eel gill. ANP binding to the gill membrane fraction was saturable with increasing ligand concentrations and was specific to ANP peptides, i.e. eANP, ventricular natriuretic peptide (VNP) and C-type natriuretic peptide (CNP). A Scatchard analysis revealed a single class of high-affinity receptors with a Kd of 59.2 pM and a Bmax of 67.9 fmol/mg protein. The Kd value is within the ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…The function of dense GCuncoupled receptors in the dogfish gill may be to regulate plasma CNP titre, as has been suggested for the trout (Olson & Duff 1993) and eel . Most of the GC-uncoupled receptors may be homodimeric NPR-C, as observed in mammalian lung (Shimonaka et al 1987) and teleost gill (Olson & Duff 1993, Donald et al 1994, Mishina & Takei 1997, because most 170 kDa receptors are converted to 90 kDa after reduction with 2-mercaptoethanol. The presence of tetrameric NPR-D was not excluded in the dogfish gill, but its population is minor as shown in eel gill (Mishina & Takei 1997).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…The function of dense GCuncoupled receptors in the dogfish gill may be to regulate plasma CNP titre, as has been suggested for the trout (Olson & Duff 1993) and eel . Most of the GC-uncoupled receptors may be homodimeric NPR-C, as observed in mammalian lung (Shimonaka et al 1987) and teleost gill (Olson & Duff 1993, Donald et al 1994, Mishina & Takei 1997, because most 170 kDa receptors are converted to 90 kDa after reduction with 2-mercaptoethanol. The presence of tetrameric NPR-D was not excluded in the dogfish gill, but its population is minor as shown in eel gill (Mishina & Takei 1997).…”
Section: Discussionmentioning
confidence: 98%
“…They weighed 0·8-2·5 kg at the time of experimentation. Membrane fractions were prepared from various tissues as described previously (Mishina & Takei 1997). The dogfish were anaesthetised by immersion in 1% tricaine methanesulphonate for 10 min and the heart was exposed.…”
Section: Preparation Of Membrane Fractionmentioning
confidence: 99%
See 2 more Smart Citations
“…A radioligand-binding assay showed that ANP receptors exist in the gills, but the predominant receptors are clearancetype NPR-C in eels (Sakaguchi et al, 1993) and toadfish (Donald et al, 1994). Further, Mishina and Takei (1997) showed that the NPR-A type is not detectable in the gills of SW eels as shown by the absence of cGMP accumulation after addition of ANP to isolated gill cells. These results provide correlative support for the absence of ANP effects on the gills of SW eels.…”
Section: Discussionmentioning
confidence: 99%